Evaluación del valor nutritivo de subproductos del camarón en la alimentación de pollos - Jarquin, R.; Braham, J.E.; Gonzalez, J.M; BRESSANI, R. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
A series of experiments with chickens was carried out for the purpose of evaluating the nutritive value of by-products from the shrimp industry. The protein content of these materials ranges from 37 to 47 per cent, and their ash content. from 29 to 34 per cent; this last fraction is relatively high in calcium and low in phosphorus. Their lysine content varies between 1.98 and 3.41 per cent. The analytical values are comparable to those of low-quality fish meals. According to the results of the feeding trials, shrimp by-products do not induce weight increases in chickens comparable to those obtained when fish meal is used at the same dietary protein level. The lysine content of the by-products was found to be biologically available, but at a lower concentration, since a response to lysine supplementation was observed with diets that contained shrimp by-products as ingredients. For these reasons, and when diets are of the types used in these studies, it is concluded that fish meal can be substituted for shrimp by-products in smaller percentages. Besides the lysine deficiency, excess of calcium in these by-products could have also been the responsible factor for their poor nutritive quality, since the addition of phosphorus improved the growth rate of the chickens.